Synthesis of dye/fluorescent functionalized dendrons based on cyclotriphosphazene - Hameau, Aurélien; Fuchs, Sabine; Laurent, Régis; Majoral, Jean-Pierre; Caminade, Anne-Marie (Beilstein Journal of Organic Chemistry, 2011)
Functionalized phenols based on tyramine were synthesized in order to be selectively grafted on to hexachlorocyclotriphosphazene, affording a variety of functionalized dendrons of type AB5. The B functions comprised fluorescent groups (dansyl) or dyes (dabsyl), whereas the A function was provided by either an aldehyde or an amine. The characterization of these dendrons is reported. An unexpected behaviour of a fluorescent and water-soluble dendron based on dansyl groups in mixtures of dioxane/water was observed.
Keywords: dabsyl; dansyl; dendrimer; dendron; fluorescence